Metabolic Engineering of Escherichia coli for Enhanced Production of Naringenin 7-Sulfate and Its Biological Activities - Chu, Luan L.; Dhakal, Dipesh; Shin, Hee J.; Jung, Hye J.; Yamaguchi, Tokutaro; Sohng, Jae K. (Frontiers in Microbiology, 2018)
Flavonoids are one of the predominant groups of plant polyphenols, and these compounds have significant effects on human health and nutrition. Sulfated flavonoids have more favorable attributes compared to their parent compounds such as increased solubility, stability and bioavailability. In this research, we developed a microbial system to produce sulfated naringenin using Escherichia coli expressing a sulfotransferase from Arabidopsis thaliana (At2g03770). This wild type strain was used as a model system for testing clustered regularly interspaced short palindromic repeats (CIRSPR) interference (CRISPRi) metabolic engineering strategies. Using synthetic sgRNA to mediate transcriptional repression of cysH, a gene encoding 3´-phosphoadenosine-5´-phosphosulfate (PAPS) sulfotransferase, which is involved in sulfur metabolism, resulted in an increase in intracellular PAPS accumulation by over 3.28-fold without impairing cell growth. Moreover, naringenin 7-sulfate production by engineering E. coli with its cysH gene repressed in the open reading frame through CRISPRi was enhanced by 2.83-fold in compared with the wild type control. To improve the efficiency of biotransformation, the concentration of SO42-, glucose and substrate were optimized. The bioproductivity of naringenin 7-sulfate was 135.49 µM [~143.1 mg (47.7 mg L-1)] in a 3-L fermenter at 36 h. These results demonstrated that the CRISPRi system was successfully applied for the first time in E. coli to develop an efficient micobial strain for production of a sulfated flavonoid. In addition, antibacterial and anticancer activities of naringenin 7-sulfate were investigated and found to be higher than the parent compound.